Reconfigured securityscapes in Louis Trichardt: Possibilities, limitations, and contradictions - Chakwizira, James (Frontiers in Sustainable Cities, 2023)
Insecurity, violence, and xenophobia affect all geographic scales of the South African landscape threatening to compromise, reverse, derail and contradict the envisaged democratic processes and gains in the country. The discussion pressure and pain points revolve around widening societal inequalities, deepening poverty, influx of (ll)legal migrants and migrant labour, lingering xenophobia, and failure to embrace the otherness difficulties in the country. In the interim, the South African landscape, has witnessed surges of different scales of violence, protests, riots, looting, criminality, and vigilantism in which question marks have been raised in respect to right to the city or urban space, right to national resources and opportunities i.e., access, use, distribution and spread of social, economic, environmental, and political resources and benefits. Louis Trichardt is a small rural agricultural town located in Makhado municipality of Vhembe District in Limpopo province, South Africa, represents a unique case in exploring urban conflict and violence making use of a securityscapes lenses of analysis. The relative importance index (RII) was used to measure the barriers and solutions to advance safe neighbourhoods settlements and built environments in the study area. In this way, issues influencing the performance of reconfigured securityscapes in Louis Trichardt were explored highlighting how new town neighbourhood securityscapes initiatives and activities are contributing to space, place, and culture change management transitions. Findings highlight the options for urban (in)security, social (in)justice and (re)design in post-colonies possibilities, limitations, and contradictions of securityscapes in (re)configured spaces of Louis Trichardt. Policy and planning proposals to improve safety and security spatial logic and innovation are explored. The critical role of community and local neighbourhood watch groups in complementing state security and private registered security systems is one way of tackling this matter.